Recycling of silicon carbide and silicon from wafer sawing slurry - Neesse, T.; Dueck, J.; Endres, E.; Jakob, L. (Publishing House of the KarSU named after E.A.Buketov, 2012)
In the production of silicon wafers for the photovoltaic industry a wafer saw cutting process is employed to slice the mono- or polycrystalline ingots to wafers. For that, multi-wire sawing using SiC slurry is the main slicing technology in photovoltaic (PV) and semiconductor (SC) industry. The cutting process produces a large quantity of saw dust (kerf). Dependent on the wafer thickness and the diameter of the cutting wire, the amount of sawing chips yields up to 30 – 50% of the ingot weight. This residue contains mainly the abrasive SiC, the Si-abrasion and Fe with other metals coming from the saw wire in a suspension of polyethylen glycol (PEG). They thus constitutes valuable materials which are well suited to be recycled to the photovoltaic industry. A solution of the waste slurry problem is unfortunate, both from an economical and environmental point of view. This paper reports on different concepts and own experiences related to Si and SiC recycling
Keywords: Si-Recycling; SiC-Recycling; Trichlorosilane; Hydrocyclone